The Effect of Insomnia on Cortical Excitability in Patients With Generalized Anxiety Disorder - Huang, Zhaoyang; Zhan, Shuqin; Chen, Chao; Li, Ning; Ding, Yan; Hou, Yue; Wang, Li; Wang, Yuping (Frontiers in Psychiatry, 2019)
The high rate of comorbidity between insomnia and anxiety disorders have been confirmed by previous studies. However, the underlying neurobiological correlates of the relationship between insomnia and anxiety disorders are largely unknown. The aim of the present study was to investigate the effect of insomnia on cortical excitability in patients with generalized anxiety disorder (GAD) by examining the recovery functions of median nerve somatosensory evoked potentials (SEPs) in patients with GAD without insomnia and patients with GAD comorbid with insomnia. We studied the recovery functions of median nerve SEPs in 12 medication-naive patients with GAD without insomnia, 15 medication-naive patients with GAD comorbid with insomnia, and 15 age and sex matched healthy controls. SEPs in response to single stimulus and paired stimuli at interstimulus intervals (ISIs) of 20, 60, 100 and 150 ms were recorded. The recovery function of the P25 component showed significantly reduced suppression in patients with GAD without insomnia as compared to patients with GAD comorbid with insomnia and healthy controls. There were no significant differences in the recovery functions of median nerve SEPs between patients with GAD comorbid with insomnia and healthy controls. The present study suggested that the cortical excitability of right parietal cortex increased in patients with GAD without insomnia, and cortical excitability in patients with GAD comorbid with insomnia was modulated by insomnia. Our findings provide new insights into the underlying neurobiological correlates of the effects of insomnia on GAD, which could ultimately be used to inform clinical intervention.